Impaired auditory discrimination learning following perinatal nicotine exposure or β2 nicotinic acetylcholine receptor subunit deletion - Horst, Nicole K. (2012)
Maternal smoking during pregnancy can impair performance of the exposed offspring in tasks that require auditory stimulus processing and perception; however, the tobacco component(s) responsible for these effects and the underlying neurobiological mechanisms remain uncertain. In this study, we show that administration of nicotine during mouse perinatal development can impair performance in an auditory discrimination paradigm when the exposed animals are mature. This suggests that nicotine disrupts auditory pathways via nicotinic acetylcholine receptors (nAChRs) that are expressed at an early stage of development. We have also determined that mice which lack nAChRs containing the β2 subunit (β2* nAChRs) exhibit similarly compromised performance in this task, suggesting that β2* nAChRs are necessary for normal auditory discrimination or that β2* nAChRs play a critical role in development of the circuitry required for task performance. In contrast, no effect of perinatal nicotine exposure or β2 subunit knockout was found on the acquisition and performance of a differential reinforcement of low rate task. This suggests that the auditory discrimination impairments are not a consequence of a general deficit in learning and memory, but may be the result of compromised auditory stimulus processing in the nicotine-exposed and knockout animals.